The Relationship between Fibromyalgia Syndrome and Body Mass Index. - Munshed, Mohammed H.; Gorial, Faiq I.; Al-Janabi, Anwar A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Fibromyalgia syndrome (FMS) is a common rheumatologic syndrome with multiple systemic manifestations & associated with many diseases. The aim of the study is to assess the relationship between FMS and BMI (Body mass index) in a sample of Iraqi patients.Patients and Methods: Fifty patients with FMS, 46 (92%) females and 4 (8%) males; their mean age (47.44), and 25 healthy control individuals were studied; 13 (52%) are females and 12 (48%) are males, their mean ages (41.4) years. All FMS features and criteria are studied for patients and control, patients with secondary FMS was excluded. Body mass index (BMI) is determined for both groups. Results: The ratio between female and male was 11:1. There was a statistical significant relation between patient with FMS and BMI (P-value= 0.001) but there was no statistical significant relation in age score between patient with FMS and BMI (P-value= 0.531). All variables which are sleep disturbance, headache, fatigue, numbness, stressful events, depression and irritable bowel symptoms have statistical significant difference between FMS patients and controls (P-value < 0.05) except anxiety which has no statistical significant relation (P-value= 0.123).The relationship between BMI and the variables in the FMS patients show no statistical significant relation (P-value > 0.05) except sleep disturbance which show significant relation (P-value= 0.045).Conclusions: There is a statistically significant relationship between FMS and increased BMI.